2020
DOI: 10.1002/pcr2.10098
|View full text |Cite
|
Sign up to set email alerts
|

In situ POM and FTIR investigation on quiescent phase transition of polybutene‐1 from form II to form I

Abstract: Despite extensive investigations in the past decade, the factors affecting the phase transition of polybutene‐1 (PB‐1) form tetragonal form II to hexagonal form I were not clarified completely. In this study, quiescent phase transitions of PB‐1 within different morphological of crystals at different temperatures were investigated employing polarized optical microscopy and Fourier transform infrared spectroscopy. Results indicate that the phase transition depends not only on intercrystalline links but also on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 66 publications
(195 reference statements)
0
6
0
Order By: Relevance
“…To accelerate phase transition, we employed two-step annealing method suggested by Men et al, i.e., lower-temperature annealing first for form I nucleation and then high-temperature annealing for form I growth. It was reported that employing such a method could reduce the phase transition time greatly. , According to the literature, , −10 and +40 °C were employed as nucleation temperature and growth temperature, respectively. Nucleation time and growth time were 120 and 230 min, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To accelerate phase transition, we employed two-step annealing method suggested by Men et al, i.e., lower-temperature annealing first for form I nucleation and then high-temperature annealing for form I growth. It was reported that employing such a method could reduce the phase transition time greatly. , According to the literature, , −10 and +40 °C were employed as nucleation temperature and growth temperature, respectively. Nucleation time and growth time were 120 and 230 min, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…A plausible explanation is that the form II to form I phase transition occurs first in thick lamellar crystals. Poly­(1-butene) normally forms a broad thickness distribution of lamellar crystals . The thick form II lamellar crystal has a lower folded-surface free energy in an unit volume, which favors a form II to form I phase transition.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations